A Cost Analysis of Paddy Transportation and Distribution Systems in the Muda Agricultural Development Authority Granary Area - Abdullah, Amin Mahir (2006)
This study attempts to develop an efficient paddy transportation and distribution systems in the Muda Agricultural Development Authority (MADA) granary area. This paddy production area is selected because it is one the largest paddy production area and it has the largest number of paddy post production participants. In order to achieve the research objectives, three analyses were undertaken; namely the descriptive analysis, modeling and estimation of transportation related cost functions using econometric models and linear programming model analysis. Cross sectional data which were obtained from survey were used to describe the characteristics of the respondents and were used to compute related costs and estimation of trucking cost, queuing cost and road charges. Survey on 741 transportation participants who were mainly lorry drivers and operators was carried out to obtain the relevant data. Data on paddy production for season 1 and 2 were obtained from MADA and data on rice mills' drying capacity were provided by BERNAS and the Ministry of Agriculture (now, the Ministry of Agriculture and Agro-based Industries). The study revealed that the majority of vehicles used to transport paddy from farms to procurement centres were between 1 to 3 tonne loading capacity. The mean load was 3.2 tonnes and the mean distance from farm to mill was 5.8 kilometers. Data analyses were conducted by three vehicles classes and they were categorized in terms of loading capacity; i. less than 1 tonne, ii. 1 to 2 tonnes, and iii. 2 to 3 tonnes. This analysis was conducted to determine the relationship between cost and vehicle size. The computed trucking cost gave the expected results, that was, trucking costs per tonne of paddy for vehicle with the sizes of less than 1 tonne, 1 to 2 tonne and 2 to 3 tonnes were RM7.75, RM6.56 and RM5.84 respectively. Survey data were then used to estimate paddy transportation costs, specifically trucking cost, queuing cost and road charges. Linear, quadratic, cubic and logarithmic functional forms were used to estimate these costs. The logarithmic function exhibited the best estimates for trucking cost and linear functional form was chosen for road charge model. Logarithmic form for trucking cost function was chosen for analysis due to its relative higher R square value and high Fstatistics as compared to other forms estimated. Linear programming based transportation model analysis was used to determine the optimal transportation cost and quantity of paddy distributed to procurement centres. The solutions revealed that 10 mills were idle in both seasons, 11 mills were idle in one of the seasons, 10 mills were allocated less than the required amount of paddy in one of the seasons, and 1 mill received paddy less than the demand in both seasons. The results illustrate the unbalanced situation between paddy production and number of rice mills in the granary. The results also implied improper planning in terms of setting up rice mills. The difference between the optimal transportation cost and the actual transportation cost indicate some level of cost efficiency of the existing system. Comparison between transportation cost and road charges provides a measurement for transportation service pricing efficiency. The model’s solutions also indicated that there was a slight difference in the average actual trucking cost and the average optimal trucking cost but a considerable difference existed between average trucking cost and average transportation service price. The small difference in the average optimal and average actual trucking cost indicated that a level of cost efficiency had been achieved. However, a considerable gap between the average cost and the average road charge denote that the farmers had been highly charged for transportation services.